ANALYSIS OF A DIFFERENTIATED APPROACH TO THE APPOINTMENT OF DICK METHODS IN BIOFEEDBACK CORRECTION AUTONOMIC DYSFUNCTION - A. G. Polyakova; V. V. Matveeva (Бюллетень сибирской медицины)
Goal of research: analysis of the effectiveness of Biofeedback therapy is differentiated depending on the clinical forms of autonomic dysfunction. Exchange rate control efficacy of biofeedback hardware was conducted on the dynamics of clinical andl aboratory data, surveys and assessment of the functional State of the SNC using heart rate variability, vegetative resonance test, Kerdo index definition, as well as èlektrokardiografiče applications and questionnaires, characterizing the State of psychoemotional sphere (Spilbergera–Hanina, test, Luscher). Laboratory tests include a complete blood count with evaluation of Adaptive reactions of the organism. The results of the rehabilitation complex of the patients with the use of biofeedback have confirmed its effectiveness.